Meditation as a Therapeutic Intervention for Adults at Risk for Alzheimer’s Disease – Potential Benefits and Underlying Mechanisms - Innes, Kim E.; Selfe, Terry Kit (Frontiers in Psychiatry, 2014)
Alzheimer's disease (AD) is a chronic, progressive, brain disorder that affects at least 5.3 million Americans at an estimated cost of $148 billion, figures that are expected to rise steeply in coming years. Despite decades of research, there is still no cure for AD, and effective therapies for preventing or slowing progression of cognitive decline in at-risk populations remain elusive. While the etiology of AD remains uncertain, chronic stress, sleep deficits, and mood disturbance, conditions common in those with cognitive impairment, have been prospectively linked to the development and progression of both chronic illness and memory loss and are significant predictors of AD. Therapies such as meditation that specifically target these risk factors may thus hold promise for slowing and possibly preventing cognitive decline in those at risk. In this paper, we briefly review the existing evidence regarding the potential utility of meditation as a therapeutic intervention for those with and at risk for AD, discuss possible mechanisms underlying the observed benefits of meditation, and outline directions for future research.